Effect of Body Weight Exercises for COVID-19 Survivors - Dubba, NagaRaju; Muthukumaran, Jothilingam; Dasarapu, Indrani (INTI International University, 2023)
Background: People recovered from the global pandemic of coronavirus disease 2019 (COVID-19) are known as COVID-19 Survivors. After recovery from COVID-19, Survivors faced multifarious health problems, still future research is required on disease and its long terms effects. Most of the COVID-19 survivors are suffering with Musculoskeletal system problems and they are affected by acute peripheral and respiratory skeletal muscle dysfunction accompanied by polyneuropathy and myopathy which resulted in decreased muscle strength, limited physical activity, impaired functional performance. Hence our study was undertaken with an intention to provide Body Weight exercises for COVID-19 Survivors to improve muscle strength.The aim of the study was to provide Body Weight exercises for COVID-19 Survivors. Method: A randomized controlled trial was conducted on covid-19 Survivors by following PAR-Q and ACSM risk stratification. Covid-19 survivors were divided into 2 groups. Group-A and Group-B based on inclusion and exclusion criteria. The subjects were fully explained about the study and after getting their consent. The outcomes used in the study were 6minute walk test, sit and reach test. Group-A was treated with conventional exercises and group-B was treated with Body Weight exercises. Result: The result of the study showed that there was a significant difference between the group -A and group-B. Statistical analysis of posttest vales of 6minute walk test and sit and reach test revealed that Covid-19 survivors who received Body Weight exercises in group-B showed marked improved compared to Group-A, the p value for both the outcomes are less than 0.001(P< 0.001). Conclusion: Statistical analysis of posttest vales of group-A and Group-B revealed that there was a significant difference between both the groups. This study concluded that both groups resulted in positive outcomes but group-B with Body Weight exercises showed higher level of positive outcome in improving muscle strength when compared with group-A.